Twisting and turning: India's telecommunications and media industries under the neo-liberal regime. (1st June 2013) - Pendakur, Manjunath
This paper traces the transformation of India's telecommunications and media industries in the context of neo-liberal policies pursued by the state since 1991 to establish the supremacy of the market.The growth of the capitalist enterprises, their expansion abroad, their entanglement with foreign capital and the closer ties to the multinationals are some of the features of this historic process. While the evidence indicates impressive short-term gains for the middle and upper classes, the larger structural questions linger. Nearly 400 million Indians out of the billion-plus population are languishing in crushing poverty as they attempt to climb up the economic ladder and grab the ephemeral promises made by the new, fast globalizing economy. The social costs of this economy, in which post-colonial India's vision of a fair and just society are abandoned, have resulted in various upheavals and an unstable political economy.